KONDISI SOSIAL EKONOMI MASYARAKAT DI SEKITAR PERTAMBANGAN NIKEL DI KECAMATAN BAHODOPI KABUPATEN MOROWALI - Ayu, Kustiana; Harafah, La Ode Muhammad; Millia, Heppi (JURNAL EKONOMI UHO, 2016)
This study aimed to reveal the socio-economic condition of the society around nickel mining located in the District of Bohodopi in Morowali Regency. Population of the study was the people in the subdistrict of Bohodopi, particularly those who lived in 4 villages, including Labota, Faturia, Keurea, and Bahomakmur. Samples were determined using the purposive sampling consists  10 respondent from  labor of mining; and 30 labor of non mining.  The data were then analyzed using a descriptive analysis. Results of the study indicated that the presence of a company in a region is expected to create a better social and economic condition and to improve the welfare of the people in the region. The improvement of social condition is reflected in the increase of people’s incomes, as well as in more employment opportunities for the local people so that they can improve their life welfare. The improvement of economic condition is reflected in the increase of facilities and infrastructures for education, healthcare, and housing, that can improve the welfare of the local people.